2011
DOI: 10.1089/jwh.2010.2053
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Insulin Resistance and Impaired Glucose Tolerance in Lean Women with Polycystic Ovary Syndrome

Abstract: Objective: To analyze insulin resistance (IR) and determine the need for a 2-hour oral glucose tolerance test (OGTT) for the identification of IR and impaired glucose tolerance (IGT) in lean nondiabetic women with polycystic ovary syndrome (PCOS). Methods: This was a cross-sectional analysis of treatment-naive women with PCOS who enrolled in a universitybased clinical trial. Nondiabetic women with PCOS based on the Eunice Kennedy Shriven National Institute of Child Health and Human Development (NICHD) definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 35 publications
(37 reference statements)
3
44
0
8
Order By: Relevance
“…confirmed by other research groups (33,34,35). Besides, it has been shown that women with PCOS display a strong positive family history of DM, another fundamental predisposing factor in DM development (36).…”
Section: Figurementioning
confidence: 53%
“…confirmed by other research groups (33,34,35). Besides, it has been shown that women with PCOS display a strong positive family history of DM, another fundamental predisposing factor in DM development (36).…”
Section: Figurementioning
confidence: 53%
“…Patients diagnosed with PCOS are included in the groups at risk of developing diabetes, in accordance with the standards of the Polish Diabetes Association. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Bu metabolik yüke bir de vücut yağ kitlesi fazlalığı olarak bilinen obezitenin eklenmesi bu sendromdan etkilenen kadınların glukoz metabolizmasının daha da fazla bozulmasına yol açar. Hatta zayıf PKOS'lu kadınlardaki insülin duyarlılığındaki azalma seviyesinin PKOS'u olmayan obes kadınlarakine benzer derecede olduğu bildirilmiştir [11][12][13] . Androjen fazlalığı cemiyeti obez PKOS'luların zayıf PKOS'lulara kıyasla tip 2 diabetes mellitus gelişim riskinin daha fazla olmasından ötürü obes PKOS'lularda olası bozulmuş glukoz toleransı veya tip 2 diabetes mellitus varlığının incelenmesi amacı ile 2 saatlik glukoz yükleme testinin rutin olarak uygulanmasını önermektedir 14 .…”
Section: Discussionunclassified